2020
DOI: 10.4314/ahs.v20i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-behavioral factors associated with neurocognitive performance among people living with HIV on antiretroviral therapy in Accra, Ghana

Abstract: Background: It is estimated that almost half of all people living with HIV have some form of neurocognitive impairment, but few studies have looked at the risk of neurocognitive impairment and its associated factors in Ghana, due in part to limited resources for such testing. Objective: To examine neurocognitive performance in a group of Ghanaians living with HIV and possible factors that contribute to their performance. Methods: One hundred and four patients were assessed using a selection of brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In this study, depression was associated with HIV-associated neurocognitive impairment, which is supported by previous findings in which depression was associated with the risk of neurocognitive impairment ( 63 , 64 ). Depression is commonly co-morbid with HIV infection, but the association is not clear on which factors may contribute to lower neurocognitive impairment ( 65 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, depression was associated with HIV-associated neurocognitive impairment, which is supported by previous findings in which depression was associated with the risk of neurocognitive impairment ( 63 , 64 ). Depression is commonly co-morbid with HIV infection, but the association is not clear on which factors may contribute to lower neurocognitive impairment ( 65 ).…”
Section: Discussionsupporting
confidence: 92%
“…These additional medications even though increase the drug burden of PLWHA are important in controlling hematological derangements and bacterial infections that are common in HIV infection. [27][28][29] Antibiotics and hematinics were however stopped when the viral load, hemoglobin level, and risk of infection were controlled to normal levels. Our results revealed that a significant number (approx.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, the prevalence of depression in PLWH can be as high as 53.4% [22]. In addition, PLWH who have depressive symptoms in Ghana are at risk of neurocognitive impairment [23]. Two qualitative studies identified ART adherence facilitators in Ghana to include having access to food, disclosure of HIV status, availability of ART, family and partner support, organization of ART clinics, and transportation cost [24,25].…”
Section: Introductionmentioning
confidence: 99%